9(t+2)=6(t-2)

Simple and best practice solution for 9(t+2)=6(t-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(t+2)=6(t-2) equation:


Simplifying
9(t + 2) = 6(t + -2)

Reorder the terms:
9(2 + t) = 6(t + -2)
(2 * 9 + t * 9) = 6(t + -2)
(18 + 9t) = 6(t + -2)

Reorder the terms:
18 + 9t = 6(-2 + t)
18 + 9t = (-2 * 6 + t * 6)
18 + 9t = (-12 + 6t)

Solving
18 + 9t = -12 + 6t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-6t' to each side of the equation.
18 + 9t + -6t = -12 + 6t + -6t

Combine like terms: 9t + -6t = 3t
18 + 3t = -12 + 6t + -6t

Combine like terms: 6t + -6t = 0
18 + 3t = -12 + 0
18 + 3t = -12

Add '-18' to each side of the equation.
18 + -18 + 3t = -12 + -18

Combine like terms: 18 + -18 = 0
0 + 3t = -12 + -18
3t = -12 + -18

Combine like terms: -12 + -18 = -30
3t = -30

Divide each side by '3'.
t = -10

Simplifying
t = -10

See similar equations:

| 0.9=-8c+0.5+9c+0.2 | | 28=m-5 | | h-2=4 | | -5(6y-6)-y=-2(y-3) | | ln(x-3)-2=8 | | 2+(-5)=x | | 2(x+4)-16=20 | | 1.5y+6= | | 2x+9=x^2 | | m+29=-52 | | x-48=-47 | | 7x-3+11x+3=162 | | 3kx^2-2kx+1=0 | | 3.6=r-2.3 | | -4x+6=2x+18 | | a^2-8=26 | | 8.2x+4=7.6x+10 | | x+3=-x-6 | | 64=-2r | | 8.2+4=7.6x+10 | | 9x^2=6-4x | | q+6whenq=12 | | 1-3/5+1/2= | | 2x^2-190x+2400=0 | | 0.50x+0.15(30)=46.5 | | -9c-5=13 | | z-7=14 | | -7=m(-6)+b | | 42+m=-21 | | -36+f=4 | | -2+3x=4x-7-x | | -1/2(6x+9)-(x-3/2)= |

Equations solver categories